Peran Kepala Sekolah dalam Peningkatan Motivasi Kerja Guru di SMP Negeri I Bungku Timur Sulawesi Tengah - Saefuddin, Saefuddin (Jurnal Paedagogy, 2020)
The purpose of this study was to determine teacher work motivation and the role of school principals in increasing teacher work motivation at SMPN I Bungku Timur. This research method uses a qualitative descriptive method with a phenomenological approach. The subjects in this study were the principal and teachers. Data collection was carried out by participant and non-participant observation, unstructured interviews and documentation. This research data analysis using qualitative descriptive analysis. The results of this study indicate that the work motivation of teachers at SMPN I Bungku Timur is quite high. This is evidenced by the commitment and loyalty of teachers who work well. This condition can be seen from their activities in carrying out their responsibilities in doing work, the achievements they have achieved, self-development and independence in acting. As for the role of the principal in increasing teacher work motivation, namely: as a work partner, participant, supporter, giving a mandate, making a fun workplace and a role model for teachers of SMPN I Bungku Timur.